Assessing the impact of a program for late surgical intervention in early-blind children. (May 2017) - Kalia, A.; Gandhi, T.; Chatterjee, G.; Swami, P.; Dhillon, H.; Bi, S.; Chauhan, N.; Gupta, S.D.; Sharma, P.; Sood, S.; Ganesh, S.; Mathur, U.; et al.
Abstract: Objective: Many blind children in the developing world are unable to obtain timely treatment due to lack of financial and medical resources. Can public health programs that identify and treat such children several years after the onset of blindness enhance their quality of life? The notion that visual development is subject to an early 'critical period' argues against this possibility. However, there are inadequate empirical data from humans on this issue. To address this need, we examined the quality of life of children living in India and who were treated for early-onset blindness (before one year of age), due to cataracts or corneal opacities. Study design: Survey study. Methods: As part of an ongoing scientific effort named Project Prakash, we screened over 40, 000 children in rural northern India to identify those suffering from early-onset blindness. They were provided eye surgeries in a tertiary care ophthalmic center in New Delhi. We subsequently surveyed 64 Prakash children, ranging in age from 5 to 22 years and obtained their responses on a multi-dimensional quality of life questionnaire. Results: Nearly all of the subjects indicated that their quality of life had improved after treatment. Children reported marked enhancement in their mobility, independence, and safety, and also in social integration. Surprisingly, we found no significant correlations between quality of life metrics and factors such as age at treatment, gender, time since treatment, and pre-surgery and post-surgery acuity. Conclusions: A key question for public health policy makers is whether a program of surgical intervention for older blind children is likely to be beneficial, or if the resources are better spent on rehabilitation via vocational training and assistive devices. The marked improvements in quality of life we find in our data strongly argue for the provision of surgical care regardless of a child's age. Highlights: We assessed the long-term impact of programs that provide surgery to older children with treatable blindness. Children across ages were surveyed on whether treatment changed their quality of life in personal and social domains. Responses indicated that treatment positively impacted children's lives and did not correlate with the age of the child. Programs that provide surgical intervention to those with treatable blindness should help children regardless of their age.